Heterogeneous effects of market integration on sub-adult body size and nutritional status among the Shuar of Amazonian Ecuador. (3rd July 2016) - Urlacher, Samuel S.; Liebert, Melissa A.; Josh Snodgrass, J.; Blackwell, Aaron D.; Cepon-Robins, Tara J.; Gildner, Theresa E.; Madimenos, Felicia C.; Amir, Dorsa; Bribiescas, Richard G.; Sugiyama, Lawrence S.
Abstract: Background: Market integration (MI)—increasing production for and consumption from a market-based economy—is drastically altering traditional ways of life and environmental conditions among indigenous Amazonian peoples. The effects of MI on the biology and health of Amazonian children and adolescents, however, remain unclear. Aim: This study examines the impact of MI on sub-adult body size and nutritional status at the population, regional and household levels among the Shuar of Amazonian Ecuador. Subjects and methods: Anthropometric data were collected between 2005–2014 from 2164 Shuar (aged 2–19 years) living in two geographic regions differing in general degree of MI. High-resolution household economic, lifestyle and dietary data were collected from a sub-sample of 631 participants. Analyses were performed to investigate relationships between body size and year of data collection, region and specific aspects of household MI. Results: Results from temporal and regional analyses suggest that MI has a significant and overall positive impact on Shuar body size and nutritional status. However, household-level results exhibit nuanced and heterogeneous specific effects of MI underlying these overarching relationships. Conclusion: This study provides novel insight into the complex socio-ecological pathways linking MI, physical growth and health among the Shuar and other indigenous Amazonian populations.